Biomass and Carbon Storage in Trees Grown under Different Agroforestry Systems in Semi Arid Region of Central India - Newaj, Ram; Chavan, S. B.; Alam, Badre; Dhyani, S. K. (Indian Forester, 2016)
The biomass and carbon storage was assessed in a well established agroforestry experiment on Albizia procera and Dalbergia sissoo under irrigated condition and Emblica officinalis and Hardwickia binata under rainfed conditions during 2011. A. procera accumulated maximum biomass (120.421 ha-1 at 11-year age) followed by D. sissoo accumulated 84.751 biomass ha-1 at age of 17-year under irrigated conditions. Similarly, biomass accumulation in E. officinalis was 14.991 ha-1 at age of 15-year and H. binata accumulated 101.341 biomass ha-1 at age of 20-year. A. procera being a fast growing tree had have higher biomass productivity (10.95 t ha-1 yr-1) followed by D. sissoo (4.99 t ha-1 yr-1) and H. binata (5.10 t ha-1 yr-1 ). E. officinalis is being a fruit bearing plant having minimum biomass productivity (1.03t ha-1 yr-1) among all the species. The carbon storage in A. procera was maximum (57.031C ha-1) followed by D. sissoo (36.621C ha-1) under irrigated conditions. Carbon storage in E. officinalis at 15-year age was 7.121 C ha-1 and in H. binata, it was 46.131 C ha-1 at 20-year age under rainfed condition.